An analysis of the Serbian poultry meat sector - Vukelić, Nataša; Rodić, Vesna; Novković, Nebojša; Bošnjak, Danica (Economics of Agriculture, 2010)
Worldwide production of poultry meat has a steady growth. In Serbia, however, there has been a significant decrease in poultry population, production and consumption of poultry meat since the early 1990s. Numerous factors contributed to the current situation. Firstly, dramatic shrinking of the market due to the disintegration of former Yugoslavia and then of the Federal Republic of Yugoslavia, followed by the UN sanctions, collapse of big poultry businesses and their unsuccessful privatisation, lack of the state support etc. The paper gives an overview of poultry meat sector in Serbia, including population, production and consumption of poultry meat, and foreign trade. The aim is to examine the current situation in Serbias poultry meat production and put forward suggestions on improving the sector.